ETIKA BISNIS ISLAM PADA ERA DISTRUPSI - Abdillah Mundir (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2020)
Business ethics has become something important in this era of increasingly fierce business competition. The number of cases of violations in the business world that have caused adverse impacts on each other, this raises the importance of awareness of business ethics. Doing business in an era of disturbances requires Islamic Business Ethics in order to achieve business benefits without destroying each other. Islam teaches to be honest, trustworthy and fair in doing business and avoid things that are manupulation, dangerous, speculative, monopolistic and hoarding, and usury. Islam provides a boundary or dividing line between what is permissible and what is not permissible, which is right and wrong as well as the halal and haram. These boundaries or lines are known as Islamic business ethics, that is ethics that is in accordance with Islamic values. Business in Islam is basically the same as business in general, it's just that they have to submit to and obey the teachings of the Qur'an, As-Sunnah, Al-Ijma and Qiyas even in the era of intense competition in the era of disruption which tend to be mutually detrimental, killing each other and nullifying each other. By holding on to Islamic Business Ethics the business competition climate in the era of disruption will be healthier to be equally successful without destroying each other in a wild competition.